Kingdom of today - Showalter, Gena (Book of Arden, 2025)
"When Arden Roosa returns to Fort Bala Royal Academy, nothing is as it was. No longer just a lady-in-training, she's now the infamous girlfriend of High Prince Cyrus Dolion-and the woman who brought down a king. Her reward? Round-the-clock guards and the attention of a royal executioner with secrets. But Arden has secrets too. As a double agent slipping between worlds to decode forbidden prophecy, she knows what's coming. Sleeping gods are stirring, and a war igniting. With only a spark, everyone will burn. But nothing goes according to plan. Grueling trials consume her days, and dangerous questions stalk her nights. Worse, Cyrus-the fierce, unshakable warrior she might love-is unraveling, losing pieces of himself, becoming a stranger right before her eyes. Desperate to save him, Arden strikes a life-altering alliance...and everything spirals. Now the gods are no longer dreaming. They're hunting. Time is running out, the end closer than anyone dares to admit. Unless Arden can stop what's coming, Cyrus will open the door to true evil-and she'll lose him forever." -- Amazon.